Pengaruh Hutan Mangrove Terhadap Reduksi Gelombang di Pantai Bama Kabupaten Situbondo dengan Pemodelan Menggunakan Delft3D - Imanda, Regita Ramadhani; Wiyono, Retno Utami Agung; Widiarti, Wiwik Yunarni (Rekayasa, 2025)
Mangrove forest in Bama Beach is one of the mangrove forests in Indonesia. Mangroves in the Bama Beach area have a function to protect various ecosystems around it from damage due to abrasion or sedimentation. Bama Beach, whose status is still in the Baluran National Park area and a tourist spot that has a beautiful charm, needs to be protected from wave damage so that wave reduction modeling research is carried out on the influence of mangrove forest width using Delft3D software. Modeling was carried out to obtain the value of energy reduction and wave height due to the presence of mangrove forests with different widths. The modeling results found that the highest significant wave height occurred on July 16, 2023 at 12:00 WIB. Mangrove forests with a thickness of 125 m can reduce wave height by 30.031% and wave energy by 48.263%. Mangrove forests with a thickness of 110 m can reduce up to 15.988% of wave height and 31.268% of wave energy. Mangroves with a thickness of 37 m can reduce up to 4.049% of wave height and 10.940% of wave energy.